Transcendental experiences during meditation practice. (23rd December 2013) - Travis, Frederick
Abstract : This article explores transcendental experiences during meditation practice and the integration of transcendental experiences and the unfolding of higher states of consciousness with waking, dreaming, and sleeping. The subject/object relationship during transcendental experiences is characterized by the absence of time, space, and body sense—the framework that gives meaning to waking experiences. Physiologically, transcendental experiences during Transcendental Meditation practice are marked by slow inhalation, along with autonomic orientation at the onset of breath changes and heightened α1 (8–10 Hz) frontal coherence. The integration of transcendental experiences with waking, dreaming, and sleeping is also marked by distinct subjective and objective markers. This integrated state, called Cosmic Consciousness in the Vedic tradition, is subjectively marked by inner self‐awareness coexisting with waking, sleeping, and dreaming. Physiologically, Cosmic Consciousness is marked by the coexistence of α1 electroencephalography (EEG) with delta EEG during deep sleep, and higher brain integration, greater emotional stability, and decreased anxiety during challenging tasks. Transcendental experiences may be the engine that fosters higher human development.